2015
DOI: 10.1039/c4ra15451g
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing gold nanoparticle seeding density on DNA origami

Abstract: DNA origami is a valuable technique in arranging nanoparticles into various geometries with a $100 nm footprint, high resolution, and experimental simplicity. Aligned nanoparticles, in addition to being used for photonics, can also be utilized to create thin metal wires with intricate and asymmetric junctions.Many factors affect the yield and density of nanoparticles attached to DNA origami structures, including the length and number of attachment sequences, the reaction ratio of nanoparticles to DNA origami, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In order to maximize LSPR, a interparticle gap of ∼2 nm was chosen in the DNA origami design. With standard functionalization procedures, it is challenging to achieve precise alignment and high yield at the same time. , For instance, when using closely spaced binding sites, single AuNPs often bind to two neighboring binding positions simultaneously. Furthermore, a large excess of AuNPs has to be used to prevent interstructure cross-linking, followed by laborious purification steps.…”
Section: Resultsmentioning
confidence: 99%
“…In order to maximize LSPR, a interparticle gap of ∼2 nm was chosen in the DNA origami design. With standard functionalization procedures, it is challenging to achieve precise alignment and high yield at the same time. , For instance, when using closely spaced binding sites, single AuNPs often bind to two neighboring binding positions simultaneously. Furthermore, a large excess of AuNPs has to be used to prevent interstructure cross-linking, followed by laborious purification steps.…”
Section: Resultsmentioning
confidence: 99%
“…If nanotubes were used as channels or tracks for transportation of molecular cargo, dynamic rearrangement of nanotube connections between termini anchored at different points on a surface or on different objects could be used to regulate when and where signals or materials are transported. Nanotubes could also serve as templates for other materials such as electrically conductive nanoparticles, and self-assembling electrical circuits that could dynamically rewire could be developed. These examples illustrate how selective, molecular scale regulation of nanostructures that direct nanotube network connectivity could induce structural changes over length scales of 10 μm or more, 1–2 orders of magnitude larger than are induced using most reconfigurable DNA nanostructures. …”
Section: Discussionmentioning
confidence: 99%
“…A common strategy for site-specific attachment of Au seeds to a DNA origami template is to use thiol-modified DNA to form Au NP-DNA conjugates [ 25 ]. Gates et al [ 65 ] investigated parameters such as time of hybridization, ratio of seeds to templates, and concentration of Mg 2+ to optimize the seeding density and yield. They found that 30–90 min hybridization times, 1.8–4.5 ratio of Au NPs per attachment location, and 70–100 mM Mg 2+ were best suited for making thinner Au NWs that appeared continuous in SEM imaging.…”
Section: Metallization Of Dna Templatesmentioning
confidence: 99%